Evaluation of the Liver and Pancreas by 2D Shear Wave Elastography in Pediatric Wilson’s Disease - Yavuz, Sibel; Pişkin, Ferhat Can; Oktay, Cemil; Soyupak, Süreyya; Tümgör, Gökhan (Turkish Journal of Gastroenterology, 2022)
Background: The primary aim of the study was to demonstrate parenchymal changes in the liver and pancreas related to copper accumulation using ultrasound in pediatric patients with Wilson’s disease and secondly, to investigate the effectiveness of two-dimensional shear wave elastography in the diagnosis of involvement of these organs. Methods: Patients with Wilson’s disease (n = 25) who were treated and followed at our center were evaluated prospectively. In addition to routine clinical assessments, eye examination, laboratory analyses, and abdominal ultrasound imaging, all patients underwent tissue stiffness measurements from the liver and pancreas (head, body and tail) by two-dimensional shear wave elastography. The data obtained from the WD patients were compared with those of age- and sex-matched healthy controls (n = 37). Results: Liver elastography measurements showed significantly increased tissue stiffness in the patient group than in control subjects (P < .001). While there was no significant difference between the groups in the tissue thickness of pancreatic head, body, and tail, tissue stiffness was significantly reduced in the patient group (P < .001). Disease duration was significantly associated and moderately correlated with liver tissue stiffness (r = 0.417, P = .038) but not significantly associated with pancreatic tissue stiffness. Conclusion: In the early stages of Wilson’s disease, parenchymal changes occur in the liver and pancreas, which cannot be detected by conventional ultrasonography imaging but may be demonstrated by two-dimensional shear wave elastography. Ultrasound elastography is an easy to use, non-invasive, and promising method that provides numerical data on the early changes in tissue stiffness, allowing for objective monitoring of Wilson’s disease patients who require lifelong follow-up. Cite this article as: Yavuz S, Pişkin FC, Oktay C, Soyupak S, Tümgör G. Evaluation of the liver and pancreas by 2D shear wave elastography in pediatric Wilson’s disease. Turk J Gastroenterol. 2022;33(2):161-167.